FINITE ELEMENT METHOD MODELLING OF STEEL SHEET PILE STRUCTURE ON DEEP FOUNDATION EXCAVATION - Lutfi, Muhamad; Berangket, Rustama; Taqwa, Fadhila Muhammad Libasut (ASTONJADRO, 2022)
Evaluation modelling of the OT-22 steel sheet pile wall with type H-350 steel strutting reinforcement in the excavation for the foundation structure with a depth of 7.50 meters was carried out to get the value of the safety factor and wall stability. The evaluation stages include subgrade investigation using the SPT method, data collection of profile steel properties used, interpretation of soil data, staged-construction modeling using the Finite Element Method (FEM) computer application, and analysis of modeling results. From the research that has been done, the value of maximum bending moment (Mmax) is 223.8 kNm/m', the magnitude of the axial force that occurs in the strut members is 22.51 kN, 121.91 kN, and 66.10 kN respectively. The value of maximum lateral displacement (Ux) is 62.4 mm. From these results, it can be concluded that the lateral displacement (Ux) that occurs is much larger than allowable displacement (Uall) 39 mm. Thus, it is necessary to modify the existing sheet pile wall system, such as to change the dimensions of the steel sheet pile, changing the dimensions of the steel strutting, or changing the distance of the steel strutting.